Implantes de proteína morfogenética óssea (Gen-pro®) e cortical óssea bovina (Gen-ox®) : histomorfologia em tíbia de ratos submetidos ao alcoolismo experimental - Buchaim, Daniela Vieira (2005)
It had known the extensive use of alcohol in excess produces changes in many corporal tissues, including at osseous tissues. It is general knowledge the quantity of osseous defects surgically created and by the many types of accidents have increased and exists a great worry in producing substances that speed up osseous neoformation and fill in these sockets. Based in the present, it had solved come true this study with the purpose to observe histologically if the mixture use of substances Gen-pro® and Gen-ox® interfere at the osseous neoformation in animals submitted to alcoholism in many concentration degrees and if the increase of alcohol concentration also interfere in this phenomenon. For this, it had been used 64 male rats (Rattus norvegicus), divided in four groups of 16 animals each one, distributed: Control group (C) animals had not received alcohol; Experimental groups I, II and III (EI, EII and EIII, respectively) animals that had been submitted to alcohol of 6%, 15% and 25%, respectively, for a period of 90 days. After this period, left tibia of all animals had been submitted to a surgery that was came true two sockets at longitudinal direction it had been at the top had not been used any substance to fill in the socket, and the inferior had been filled in with a mixture of Gen-pro® and Gen-ox®. Four animals of each group had been sacrificed in a period of 10, 20, 40 and 60 days, counted from the day of the experimental surgery, to withdraw part of the tibia, where the surgical store had been came true. The withdraw blocks had been processed histologically and had been submitted to he HE stain and Masson trichromic, to observation and evaluation of osseous neoformation.